Temporomandibular dysfunction and neck pain: comorbid conditions? - Moreira, Alexandre Bittencourt; Morete, Marci; Cordon, Francisco; Malezan, William Rafael (Journal of Health Care, 2016)
Introduction: Neck pain is the most common symptom found in cervical disorders and is often related to inadequate postures. The rates of such disorders have increased in recent years. It is estimated that about 50% of adults will experience neck pain at some point in their life. Objective: Within this context, the present study undertakes a literature search to elucidate if temporomandibular dysfunction and neck pain could be considered as comorbidities. Materials and methods: The research was based on an integrative literature review related to neck pain and temporomandibular disorders as comorbidities. It was carried out using the following keywords: headache; neck pain; temporomandibular joint disorders; tinnitus. Results: We found a total of 4,804 articles with individual descriptors. These studies were taken from PubMed database (2,526 articles), LILACS (652 articles), BBO (416 articles) and IBECS (218 articles). After a meticulous selection, observing the criteria for inclusion and exclusion, we came up with 12 articles for this research. Conclusions: More research should be made toidentify the systemic comorbidities related to temporomandibular disorders and orofacial pain, aiming to develop a holistic and assertive treatment in shorter time.